Проблеми формування та використання бренда українськими підприємствами - Кифяк, Олександр; Ротар, Артур (Чернівецький нац. ун-т, 2018)
The report raises topical issues related to the need for the formation and effective use of the brand as one of the most progressive marketing tools for improving competitiveness. The authors also identify the main problems that slow down the development of branding by Ukrainian entrepreneurs.
Keywords: Бренд, імідж, підприємство, маркетинг